Seroprevalence of contagious bovine pleuropneumonia (CBPP) in cattle from Karamoja region, North-eastern Uganda - Tweyongyere, Robert; Nkamwesiga, Joseph; Etiang, Patrick; Mugezi, Israel; Wamala, Henry; Wasswa, Auther Tamale; Kamusiime, Maureen; Ainebyoona, Solomon; Abizera, Harriet; Mwiine, Frank Norbert; Muhanguzi, Dennis (BioMed Central Ltd, 2024)
Background Contagious bovine pleuropneumonia [CBPP] is a transboundary animal disease of cattle caused by Mycoplasma mycoides subsp. mycoides [Mmm]. CBPP causes severe economic losses to livestock producers in sub-Saharan Africa mainly due to high mortality, morbidity, reduction in productivity as well as livestock trade restrictions. This study aimed at determining seroprevalence of Mmm in cattle from Karamoja region, north-eastern Uganda; data that are required to design and implement risk based CBPP control program. Methods We randomly collected blood samples from 2,300 cattle spread across Karamoja region. Serum was extracted and screened for antibodies against Mycoplasma mycoides subsp. mycoides [Mmm] using the competitive enzyme linked immunosorbent assay [cELISA]. Results A quarter [25.4%; 95% CI: 23.7-27.3] of the screened cattle [n = 2,300] were sero-positive for Mmm. Amudat and Kaabong districts recorded the lowest [12.3%] and highest [30.7%] Mmm seroprevalence respectively. Increasing age, overnight stay in cattle kraals and location [certain districts, villages, herds and sub counties] of the cattle herds, the factors that promote animal commingling, were the most significant risk factors of seroconversion with Mmm. Conclusion Results from this study indicated a higher seroprevalence of Mmm in Karamoja region cattle herds. This could be due to the increased frequency of CBPP outbreaks in recent years. To be effective, CBPP vaccination programs should target high risk herds along the international borders and other hotspot areas [e.g., parishes or sub counties] where cattle commingling is high. Keywords: Karamoja region, Uganda, Seroprevalence, CBPP, cELISA, Cattle